Kepemimpinan Pengajaran Pegetua Sekolah Menengah Agama terhadap Pencapaian Prestasi Akademik Pelajar - Ishak, Othman (2004)
This research is carried out to analyze the connection between the leadership of school principal and the academic performance of students. Data is collected from secondary school which involved 250 people in answering 5 evaluation instruments regarding principal's behavior. The behavioural patterns are about how principals set the school's target @ objective, supervision of the teaching and learning process, encouragement in using the resource center, and human resource development. Data on the respondents' demography is also collected. Only 230 (92%) questionnaires where returned to the researcher. Spearman correlation analysis was used to test 6 null hyphotheses which indicate that there is no correlation between (i) the influence of principal's leadership in setting the school's targets @ objectives. (ii) the influence of principal's leadership in supervising and evaluating teachers in classrooms. (iii) the influence of principal's in managing the use of teaching materials. (iv) the influence of principal in using teaching material. (v) the influence of principal in managing human resource. (vi) the influence of principals' leadership and students' academic performance with the respondents demographic factor. The research also revealed that there is a significant difference in the influence of principal's leadership setting the school's objective, the influence of principal's leadership in supervising and evaluating teachers in classrooms, the influence of principal's leadership in managing teaching materials, the influence of principal's leadership in managing human resource. The research also shows that there is a significant relationship between the principal's leadership and the respondent's job and duration of service.